Benefits of 100% human milk diet in preterm infants: NICU Nurses Survey - Mohit Sahni; Prathap Chandra; Deepa Mohan Sharma; Ranjan Kumar Pejaver; Betty Thomas; Flavia Cardoza; Vikram Reddy K. (Pediatric Review: International Journal of Pediatric Research, 2020)
Background: Hundred percent human milk diet plays a vital part in the nutritional management of preterm infants in the Neonatal Intensive Care Unit (NICU). NICU nurses play an important role in the management of nutrition and growth of preterm infants, who will also oversee the implementation of an exclusive human milk diet (EHMD) in the NICU.Objective: To understand the NICU nurses' perspectives on the benefits of 100% human milk diet through human milk-derived nutritional products in preterm infants.Material and Methods: Online survey was conducted through Google Forms which had nine questions on the benefits of human milk-based nutrition finalized by expert neonatologists. An online survey link was shared with the NICU nurses through emails and text messages. A request was made to the neonatologists and head nurses to disseminate the survey link with their counterparts and colleagues.Results: All the participants rated that exclusive breastfeeding or using 100% Human Milk Diet is very important for preterm babies in NICU [n=152 (100%)]. 46.7% (n=71) participants reported that seventy calories pasteurized human breast milk, (PHBM – 70 Cal) is the best option for preterm infants when the mother’s own milk (MOM) is unavailable. 84.9% (n=129) of the participants stated that the Human milk-based fortifier (HMDF) – Mother’s Milk Fortifier (MMF) is the best option for fortification. 96% (n=146) participants were satisfied with the safety and tolerance of 100% human milk-based products like PHBM - 70 calories and MMF.Conclusion: The majority of the NICU nurses in India are aware of the benefits of human milk and 100% human milk diet in preterm infants. Human milk-derived nutritional products; HMDF (MMF) and 70 Calories are reported to be having good tolerance and safety in preterm infants by most of the NICU nurses. Having regular training sessions about EHMD for NICU nurses would be impactful.